Masterpieces of French literature - Severson, Marilyn S. (Westport, Connecticut Greenwood Press, 2004)
"Provides a critical introduction to landmark novels in nineteenth- and twentieth-century French literature. Includes works that cover a time period of over 100 years and reflect both the development of the French novel during the era as well as themes, characters, and plots that appeal to readers in the twenty-first century."--GVRL description.
The stranger, 1942 / Albert Camus -- The plague, 1947 / Albert Camus -- The three musketeers, 1844 / Alexandre Dumas -- The count of Monte Cristo, 1845 / Alexandre Dumas -- Madame Bovary, 1857 / Gustave Flaubert -- The hunchback of Notre-Dame, 1831 / Victor Hugo -- Les miserables, 1862 / Victor Hugo -- The Little Prince, 1943 / Antoine de Saint-Exupery.
Electronic reproduction.
Keywords: French fiction -- 19th century -- History and criticism; French fiction -- 20th century -- History and criticism; Electronic books